PENGEMBANGAN MEDIA BLOG SEBAGAI SARANA INFORMASI UNTUK MENINGKATKAN KEMAMPUAN PERENCANAAN KARIR DI SMAN 1 BULUKUMBA - Andi Fatmawati (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
This research is a Media Development Blog as a Means of information to enhance the planning careers in SMAN 1 Bulukumba that berujuan: (1) to describe the career guidance needs of students at SMA Negeri 1 Bulukumba); (2) to determine the profile of media use blogs as a means of information in improving the ability of career planning at SMA Negeri 1 Bulukumba); (3) to determine the effectiveness of blogs as a means of information media in enhancing the ability of career planning at SMA Negeri 1 Bulukumba. This study uses research and development developed by Dick & Carey. Analysis of data using statistical analyzes non-parametric Wilcoxon signed ranks test. The results showed (1) Career Guidance blog has utility value, feasibility and accuracy; (2) blog career guidance both as a means of career information for students at SMA Negeri 1 Bulukumba; (3) blog Career guidance is effective as a means of information in improving the ability of career planning at SMA Negeri 1 Bulukumba.